Morphological variation of Aceh Pinus (Pinus merkusii) - Andini, R.; Melinda, V.; Pardede, E.; Yanti, L.A.; Hmon, Khaing; Moulana, R.; Indrioko, S. (2022)
The genus Pinus is classified as one of the most widely distributed genera of conifer trees, that are majorly distributed in the Northern and Southern hemispheres. Pinus merkusii is the only member of the genus Pinus that is adapted in the tropics and grows naturally in south Equator. Its natural distribution found through-out Southeast Asia, e.g. in Indonesia; particularly on Sumatran Island. Three native strains are known on Sumatra: Aceh, Kerinci, and Tapanuli; with the first one is known as the largest population among the three and grows naturally on the high altitudes. The wood has been utilized in building construction, while the resin collected is classified as one of the most valuable Non Timber Forest Products (NTFP) worth up to US 50 million/year and applied in many industries. Planting of citron grass (Cymbopogon sp.) has been 'booming' over the past seven years in the middle regions of Aceh due to its attractive selling price. As consequences, many Pinus trees have been logged and demanded as fire woods in the distillation process of citron grass. Thus, the citron grass' plantation has been directly threatening the existence of Pinus forests. Therefore, in-situ conservation effort should be started from now on. Here, we would like to report the morphological variation (N= 15 traits) of natural Pinus (e.g., plant height, diameter of main stem, number of crowns per branch, etc.). The morphological data collected were then analysed with the Principal Component Analyses (PCA), in order to cluster the major agronomical parameters among them. This morphological data would be complemented and benefitted the efforts in the genetic study of Aceh Pinus. © Published under licence by IOP Publishing Ltd.